Correlating structural and mechanical properties of AlN/TiN superlattice films. (May 2019) - Koutná, Nikola; Řehák, Petr; Chen, Zhuo; Bartosik, Matthias; Fallmann, Markus; Černý, Miroslav; Zhang, Zaoli; Friák, Martin; Šob, Mojmír; Mayrhofer, Paul H.; Holec, David
Abstract: Combining first-principles and experimental techniques, we establish Young's modulus dependence of AlN/TiN superlattices on the film-forming phases, their thicknesses and crystallographic orientations. The disparate character of cleavage properties within different layers of the superlattice—providing indications regarding crack initiation processes—is linked to the changes in bond lengths. Such changes present a direct consequence of the predicted interplanar spacing oscillations which are experimentally confirmed by high resolution transmission electron microscopy analyses. Graphical Abstract: Unlabelled Image